Penatalaksanaan Fisioterapi pada Kasus Development Delay: Case Report - Tiara Fairuz Firdausi; Totok Budi Santoso; Salma Muazzaroh (Pusat Riset dan Inovasi Nasional, 2025)
Growth and development have similarities in change. And these changes involve all physical members, motor skills and language development. If there are abnormalities in the child's growth and development process, then the child will experience delays in growth and development which is usually called Developmental Delay. This study aims to determine the effect of play therapy on the growth and development of children with developmental delay conditions. This research uses the case study method. After carrying out therapy 8 times, the results showed that play therapy had an effect on improving gross motor skills and improving balance in children with developmental delay. Examination of children's motor skills using the DDST (Denver Development Screening Test) revealed an increase in several stages of ability development in gross motor aspects. Examination of the child's balance using the PBS (Pediatric Balance Scale) showed an increase in balance in several categories, such as the child being able to stand independently and turning 360°.